2012
DOI: 10.3747/co.19.1182
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Integrative Oncology Programs

Abstract: ConclusionsThe research literature documents a growing number of integrative oncology programs. These programs share a common vision to provide whole-person, patient-centred care, but each program is unique in terms of its structure and operational model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 41 publications
0
43
0
1
Order By: Relevance
“…[12] Up to 93% of people use CAM during their cancer experience,[34567] yet few resources exist, including knowledgeable health professionals or appropriate, and inclusive models of care, to support safe and effective CAM use by cancer patients. Despite these and other challenges, Canadian oncology nurses are taking a leadership role in shaping the integration of CAM into cancer care in this country.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Up to 93% of people use CAM during their cancer experience,[34567] yet few resources exist, including knowledgeable health professionals or appropriate, and inclusive models of care, to support safe and effective CAM use by cancer patients. Despite these and other challenges, Canadian oncology nurses are taking a leadership role in shaping the integration of CAM into cancer care in this country.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients are increasingly using CAM, and the number of IO programs is growing internationally [10,13,14]. On average, about 40% of all people suffering from cancer in Western industrialized countries use CAM alongside their oncological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In response to that, the field of integrative oncology (IO) has emerged, a discipline that embraces conventional and evidence-based complementary therapies. IO represents a more holistic approach to oncological treatment [8,9,10] which considers all factors that affect health, including mind, emotions, lifestyle, and body [9,11]. The spectrum of IO is broad and may encompass supportive care services such as nutritional and psychological counseling or sports rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to implement a Canadian integrative oncology research agenda were identified, and working groups are actively developing projects in line with those administrative, operating, and funding structures and concluded that there is no "gold standard" model 8 .…”
Section: Resultsmentioning
confidence: 99%